Factors Associated With Failure of Nonoperative Treatment in Lateral Epicondylitis. (September 2015) - Knutsen, Elisa J.; Calfee, Ryan P.; Chen, Raymond E.; Goldfarb, Charles A.; Park, Kevin W.; Osei, Daniel A.
Background: Lateral epicondylitis is a common cause of elbow pain that is treated with a variety of nonoperative measures and often improves with time. Minimal research is available on patients in whom these nonoperative treatments fail. Purpose: To identify baseline patient and disease factors associated with the failure of nonoperative treatment of lateral epicondylitis, defined as surgery after a period of nonoperative treatment. Study Design: Case control study; Level of evidence, 3. Methods: A total of 580 patients treated for lateral epicondylitis at a tertiary center between 2007 and 2012 were analyzed. Disease-specific and patient demographic characteristics were compared between patient groups (nonoperative vs surgical treatment). A multivariable logistic regression model was created based on preliminary univariate testing to determine which characteristics were associated with failure of nonoperative treatment. Results: Of the 580 patients, 92 (16%) underwent surgical treatment at a mean of 6 months (range, 0-31 months) from their initial visit. Univariate analysis demonstrated a potential association ( P < .10) between operative management and the following factors at initial diagnosis: increased age, body mass index, duration of symptoms, presence of radial tunnel syndrome, prior injection, physical therapy, splinting, smoking, workers' compensation, a labor occupation, use of narcotics, use of antidepressant medications, and previous orthopaedic surgery. In the final multivariable model, a workers' compensation claim (odds ratio [OR], 8.1), prior injection (OR, 5.6), the presence of radial tunnel syndrome (OR, 3.1), previous orthopaedic surgery (OR, 3.2), and duration of symptoms >12 months (OR, 2.5) remained significant independent predictors of surgical treatment. Conclusion: This study identifies risk factors for surgical treatment for lateral epicondylitis. While these findings do not provide information regarding causal factors associated with surgery, these patient and disease-specific considerations may be helpful when counseling patients regarding treatment options and the likelihood of the success of continued nonoperative treatment.